THE EFFECT OF INNOVATION, MARKET ORIENTATION, AND KNOWLEDGE MANAGEMENT ON COMPETITIVE ADVANTAGE AND COMPANY’S PERFORMANCE AT PT. TELKOMSAT CENTRAL OFFICE JAKARTA - Marwanto Tumonglo; Syamsu Alam; Muhammad Sobarsyah (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This research aims to determine the effect of innovation, market orientation, and knowledge management on company’s performance with competitive advantage as mediating variable at PT. Telkomsat central office of Jakarta as the object of research. This research was a quantitative study using validity test, reliability test, descriptive analysis, and path analysis techniques. The samples were the employees of PT. Telkomsat central office, Jakarta consisting of 73 respondents. The data were obtained using questionnaire and interview and they were processed using SPSS 23 software. The result of the research indicate that innovation and market orientation have a positive and insignificant effect on competitive advantage; knowledge management has a positive and significant effect on competitive advantage; innovation has a positive and significant effect on company’s performance; market orientation has a positive and insignificant effect on company’s performance; knowledge management has a positive and significant effect on company’s performance; competitive advantage has a positive and insignificant effect on company’s performance; innovation indirectly has a positive and insignificant effect on company’s performance through competitive advantage; market orientation indirectly has a positive and insignificant effect on company’s performance through competitive advantage; and knowledge management indirectly has a positive and insignificant effect on company’s performance through competitive advantage.